ChemInform Abstract: Gold‐Catalyzed Intramolecular Cyclization of Alkynones with Pyridine Anhydrobases. Issue 11 (18th March 2014) - Pawar, Lokesh; Pigge, F. Christopher
Abstract Acylation of alkynone substrates followed by benzylic deprotonation produces anhydrobase intermediates which undergo endo‐dig cyclization to afford pyridyl substituted γ‐ and δ‐lactams.